Implementation Of Cooperative Learning Method Type Jigsaw For Improving Skill Of Speaking English Of Cadet At Barombong Maritime Polytechnic Makassar - Ratno; Jein Novita C Budiman; Fahri Ihsan (Politeknik Pelayaran Barombong, 2022)
The purpose of this study is to know the effectiveness of implementation of cooperative learning method type jigsaw to improve skill of speaking English of cadet at Barombong Maritime Polytechnic (Politeknik Pelayaran Barombong) through a class action research (penelitian Tindakan kelas) during 3 cycles.Based on the result of research, researcher is able to conclude that implementing cooperative learning method type Jigsaw effectively improving skill of speaking English. This can be seen from scoring result in every cycle getting higher. The score in cycle II is higher than score in cycle I, while the score in cycle III is higher than score in cycle II. Finally, researcher is able to state “If cooperative learning method type Jigsaw is implemented in English class, the skill of speaking English of student will be improved”.